Energy and Exergy Analyses of a Bulk Carrier Diesel Generator for Different Loads - Kokkulunk, Gorkem (CHAMBER MARINE ENGINEERS, 2019)
Energy is the ability to do work of the systems. Exergy is defined as the availability of energy or the maximum work to be done. In this study, energy and exergy analyses of a turbo charged marine diesel generator is conducted for the loads of 25%, 50%, 75% and 100%. As a result of energy and exergy analysis, the first and second law efficiencies of a engine at 25%, 50%, 75% and 100% load conditions are calculated as 34.29%, 39.69%, 42.01%, 42.49% and 38.36%, 44.38%, 46.8% and 47.04%, respectively. The maximum shaft power values are 744.1 kW and 1058.2 kW for 50% and 75% loads, respectively. Considering the exergy values which means the available energy, the highest potentials are found as 55.7 kW at maximum load in the exhaust gases and 160.9 kW at maximum load in the cooling water. The exergy values that can be recovered from the surrounding and lubricating oil are big enough not to be neglected.
Keywords: Ship; Energy; Exergy; Diesel Generator; ENGINE; Engineering; Transportation